Electroanalytical Immunotool to Determine Matricellular Protein Periostin, a Stromal Biomarker of Prognosis in Colorectal Cancer - Marina Blázquez‐García; Jennifer Quinchia; Víctor Ruiz‐Valdepeñas Montiel; Rebeca M. Torrente‐Rodríguez; Verónica Serafín; María Garranzo‐Asensio; Ana García‐Romero; Jahir Orozco; Rodrigo Barderas; José M. Pingarrón; Susana Campuzano (ChemElectroChem, 2024)
Abstract Tumor‐associated stroma biomarkers are emerging as key signaling molecules of metastasis in colorectal cancer (CRC). In this sense, periostin (POSTN), a protein of the extracellular matrix from the stromal compartment, is envisioned as a potential stromal prognostic biomarker, which facilitates the application of pertinent treatments. In this work, we report an easy‐to‐handle amperometric sandwich‐based immunosensing strategy for the determination of POSTN involving commercial magnetic microparticles (MBs), disposable carbon electrodes, and the horseradish peroxidase (HRP)/H2O2/hydroquinone (HQ) electrochemical system. The method allowed a dynamic linear range between 0.47 and 25 ng mL−1 and a limit of detection, LOD, of 0.14 ng mL−1 compatible with clinical demands. The method was applied to the analysis of POSTN in a variety of cancer‐related real bio‐scenarios including cell extracts and secretomes from CRC cells, and plasma from CRC patients at different stages. The potentials of this firstly developed MBs‐assisted immunoplatform are justified by distinguishing between metastatic abilities of cultured CRC cells through the analysis of their extracts and secretomes, and by differentiating between healthy controls and CRC patients in just 60 min. Therefore, the developed immunoplatform can be envisaged as a novel and profitable tool for exploring the most uncharacterized but prospective tumor areas.